CHANGE MANAGEMENT STRATEGIES RELATED TO THE GLOBAL ENVIRONMENT COMPLEXITY - DOVAL, Elena (Annals of Spiru Haret University. Economic Series, 2016)
The changes in organizations appear as a reaction to the organizational environment changes. In order to manage these changes successfully, the managers need to anticipate and design alternative strategies by preparing different options. Nevertheless, the complexity of the global environment forces the managers to adopt strategies for their organizations that are facilitating the creation of new strategic competences and competitive advantages to face the environmental rapid changes. In this context, this paper is aiming to illustrate the main directions the change management may consider to change the organization strategies in order to harmonize them to the external environment, such as: integration versus externalization, flexible specialization and flexible organization, standardization versus adaptation, market segmentation, relationship building and maintaining and communication integration. However, the new strategies are based on a changed attitude of the managers towards the competitive advantage that is dynamic and focused on creation rather then to operations.